CARDIO-SELECTIVE Β-BLOCKER BISOPROLOL IN THE MANAGEMENT OF CORONARY HEART DISEASE - V. P. Lupanov (Российский кардиологический журнал)
The article is focussed on the role of a modern selective β-blocker bisoprolol in the management of coronary heart disease (CHD). The benefits of bisoprolol therapy are demonstrated for both clinical improvement and reduction in the risk of cardiovascular morbidity and mortality.